The 2020 Annual Report of the Kansas Poison Control Center at The University of Kansas Health System : 2020 KSPCC Report - Thornton, Stephen L; Oller, Lisa; White, Kathy; Coons, Doyle; Silver, Elizabeth (Kansas Journal of Medicine, 2022)
Introduction. This is the 2020 Annual Report of the Kansas Poison Control Center (KSPCC) at The University of Kansas Health System. The KSPCC receives calls from the public, law enforcement, health care professionals, and public health agencies. Methods. Encounters reported to the KSPCC from 01/01/2020 through 12/31/2020 were analyzed for caller location, demographics, exposure substance, nature of exposure, route of exposure, interventions, medical outcome, and location of care. Encounters were classified as human or animal exposure, confirmed non-exposure, or information call (no exposure). Results. There were 19,780 total encounters, including 18,492 human exposure cases. These cases were primarily female (53.6%, n = 9,911) and pediatric (19 years of age or less). (59.5%, n = 10,995). Acute cases (82.7%, n = 15,294), unintentional exposures (73.8%, n = 13,643) and ingestions (85.9%, n = 15,901) were most common. The most common reported substance was household cleaning products (n = 937) in pediatric (children ≤ 5) and analgesics (n = 1,335) in adults. An increase in exposures to disinfectants and household cleaning products was seen. Moderate (n = 1,812) or major (n=482) clinical outcomes were seen in 12.4% of cases. There were 18 deaths in 2020 reported to the KSPCC. Conclusions. Over 18,400 exposures were managed by the KSPCC in 2020. Pediatric exposures remained the most common encounter. An increase in exposures to disinfectants and other household cleaning products was seen. This report supports the continued value of the KSPCC to both public and acute health care in the state of Kansas.